Transition to Adulthood in Spina Bifida: Changing Roles and Expectations - Shubhra Mukherjee (The Scientific World Journal)
Survival to adulthood for people with Spina Bifida now exceeds 85% due to improvements in medical and surgical management. Rates remain lower than expected for community participation, healthy lifestyle choices, employment and independent living. The importance of transition programming to help adolescents with disabilities prepare for adult life roles is now understood. Literature currently is mainly conceptual or descriptive, but informs the process of developing transition program models. The need for competent and effective adult care providers is discussed. Both the transition to adulthood and the transfer of care to adult care clinics are important and distinct components of spina bifida lifespan care.